Sex differences in mechanisms of arterial stiffness - DuPont, Jennifer J. (Br J Pharmacol, 2019)
Arterial stiffness progressively increases with aging and is an independent predictor of cardiovascular disease (CVD) risk. Evidence supports that there are sex differences in the time course of aging‐related arterial stiffness and the associated CVD risk, which increases disproportionately in postmenopausal women. The association between arterial stiffness and mortality is almost twofold higher in women versus men. The differential clinical characteristics of the development of arterial stiffness between men and women indicate the involvement of sex‐specific mechanisms. This review summarizes the current literature on sex differences in vascular stiffness induced by aging, obesity, hypertension, and sex‐specific risk factors as well as the impact of hormonal status, diet, and exercise on vascular stiffness in males and females. An understanding of the mechanisms driving sex differences in vascular stiffness has the potential to identify novel sex‐specific therapies to lessen CVD risk, the leading cause of death in males and females. LINKED ARTICLES: This article is part of a themed section on The Importance of Sex Differences in Pharmacology Research. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v176.21/issuetoc